STRATEGI KOMUNIKASI: SEBUAH SOLUSI BAGI PERMASALAHAN KOMUNIKASI - Marsakawati, Ni Putu Era (English Department FBS UNP, 2012)
Communication strategies have been discussed by many linguists and researchers for ages. They described types of communication strategies employed by a particular person when he/she had problems in communicating with others. It seems that communication strategies are only employed for those who have lack knowledge of English. However, the fact still reveals that people who have good English also perform types of communication strategies. This article then aims at proving that communication strategies are also employed by speakers who are capable enough in English.Â